PENGARUH KONSENTRASI AIR REBUSAN DAUN MELINJO (Gnetum Gnemon L.) TERHADAP TOTAL MIKROBA KERABANG DAN SPECIFIC GRAVITY TELUR AYAM RAS - Suharyanto; Edi Soetrisno; Riza Surya Islamiati (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2021)
AbstractThis study aimed to determine the effect of soaking broiler eggs into boiled water of melinjo (Gnetum gnemon L.) leaves with different concentrations on the total microbial shell and Specific Gravity of broiler eggs. This research was conducted at the Laboratory of Animal Husbandry, Department of Animal Husbandry, University of Bengkulu and UPTD Laboratory of Veterinary Public Health at the Department of Animal Husbandry and Animal Health Bengkulu Province. The research used was a completely randomized design (CRD) with 4 treatments and each design consisted of 4 replications. P0: Control chicken eggs without soaking in boiled water of melinjo leaves (ARDM). P1: (ARDM) 15%. P2: (ARDM) 30%. P3: (ARDM) 45%. The variables observed in this study were the percentage change in egg weight, the percentage of egg shell weight, specific gravity and TPC (Total Plate Count) of broiler eggs. The results showed that broiler eggs soaked with boiled water from melinjo leaves at a concentration of 15% - 45% had a significant effect (P<0.05) on the difference in the proportion of egg weight on the 21st day. However, there was no significant effect (P>0.05) on the proportion of shell weight, specific gravity and TPC (Total Plate Count) of broiler eggshells. Immersion of broiler eggs using boiled water of melinjo leaves was not able to reduce the number of egg shells, but was able to distinguish differences in egg weight, shell weight and could produce 21 days of storage compared to eggs without air soaking boiled melinjo leaves (control). Keywords: broiler eggs, melinjo leaves, Specific gravity, TPC (Total Plate Count)